Honey for generations: Farmer FIRST Programme promoting beekeeping in Punjab - Singh, Kuldeep; Singh, Jaspal; Kumar, Pankaj; Singh, Dalbeer (Indian Farming, 2022)
Close interaction and encouragement along with skill development can do the miracles. It is always difficult to take the first step because of state of mind is in inertia or resistance due to various socio-economic factors. Farmer FIRST Programme efforts accelerated the knowledge,capabilities, innovativeness, risk-taking capacity and gave the motivation to start a new venture. Under the farmer FIRST Programme, PAU scientist trained the farmers in the adopted village of Sangrur (Punjab) regarding beekeeping and continuously made the efforts to enhance the adoption. As a result, a number of farmers are cultivating the sweet harvest of the enterprise and are getting handsome additional income from the enterprise without putting the pressure on existing resources. Farmers have produced about 22.50 kg/box of honey on average and sold it at an average price of `300/kg, which resulted in gross returns of `6750 per box. Thus, on an average, farmers fetched the net returns of `4475 per box. The progressive farmers among these are getting about `3–4 lakh income from the beekeeping enterprise. So, it can be summarized that FFP has created a positive impact on the livelihood of the farmers by successful introduction of honey bee enterprise.